New species of Middle Asian Longitarsus Latreille with discussion of their subgeneric placement (Coleoptera: Chrysomelidae) - Konstantinov, Alexander S. (Zootaxa, 2005)
The subgenus Testergus Weise of Longitarsus Latreille is redefined based on the characters of male genitalia and four new species are described and illustrated: L. borisi sp. nov. (Tadzhikistan), L. danilevskyi sp. nov. (Kazakhstan), L. igori sp. nov. (Tadzhikistan), and L. nadiae sp. nov. (Kirgizstan). The lectotypes for L. fuscoaeneus Redtenbacher, L. tmetopterus Jacobson and L. nurataicus Palij are designated. A key to the known Testergus species from Greece, Caucasus and Middle Asia is provided.